Enhancing Scientific Literacy Through Ethnoscience Based Pop-Up Books: A Pre-Experimental Study in Elementary Education - Supriyati Fatma Rabia; Yakub Taba; Nurbaiti Elita Genc (Jurnal Papeda: Jurnal Publikasi Pendidikan Dasar, 2026)
Scientific literacy is a foundational competency for 21st-century learners, yet Indonesia consistently ranks among the lowest performers in international assessments such as PISA. This study aimed to examine the effect of ethnoscience-based pop-up books on the scientific literacy of Grade 4 students at SDN 37, Kabupaten Sorong, Southwest Papua. Employing a one-group pretest-posttest design with total sampling (n = 8), the study used an existing pop-up book integrating local Papuan ethnoscience knowledge, specifically traditional medicinal plants (Piper betle, Curcuma longa, and Zingiber officinale var. rubrum), into science content aligned with the national curriculum. Data were collected through a 20-item multiple-choice scientific literacy test based on three PISA indicators: (1) explaining phenomena scientifically, (2) evaluating and designing scientific inquiry, and (3) interpreting data and evidence. Instrument validity was confirmed by two science education experts, and data normality was verified using the Shapiro-Wilk test. Results demonstrated an increase in mean scores from 47.50 (pretest) to 78.13 (posttest), yielding an average N-gain of 0.58 (moderate category). A paired-sample t-test confirmed statistical significance (t = 10.32, df = 7, p < 0.001). These findings indicate that ethnoscience-based pop-up books demonstrated a moderate improvement in students' scientific literacy by bridging local cultural knowledge with formal scientific concepts, offering a non-digital pedagogical strategy for remote elementary schools in eastern Indonesia.